2016
DOI: 10.3389/fpsyg.2016.01554
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Psychological Well-being and Coping Strategies among University Students

Abstract: In the transactional model of stress, coping responses are the key to preventing the stress response. In this study, the possible role of psychological well-being as a personal determinant of coping strategies in the academic context was analyzed. Specifically, the study has two objectives: (a) to identify different profiles of students according to their level of psychological well-being; and (b) to analyze the differences between these profiles in the use of three coping strategies (positive reappraisal, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 51 publications
7
67
2
14
Order By: Relevance
“…It is also important to analyse perceived inconsistencies in hypothetical relationships. In addition, the analyzed variables should be inserted into current learning strategies models, due to the potential of their contribution to knowledge of the role of meta-motivational and meta-affective strategies during university learning and health problems, produced by a maladjusted way of facing academic demands (Fernández-González et al, 2015; Freire et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It is also important to analyse perceived inconsistencies in hypothetical relationships. In addition, the analyzed variables should be inserted into current learning strategies models, due to the potential of their contribution to knowledge of the role of meta-motivational and meta-affective strategies during university learning and health problems, produced by a maladjusted way of facing academic demands (Fernández-González et al, 2015; Freire et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study involving university students also showed gender-related differences. 6 A study assessing the correlation between stress and coping strategies among college students in the USA showed that higher interpersonal stress caused greater use of disengagement coping strategies. 30 The results of our study are similar: respondents with a high level of stress revealed self-blame, behavioral disengagement and substance use more often than lessstressed individuals.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…1 The skill of coping with stress influences quality of life and mental well-being. 5,6 Insomnia, an insufficient amount of sleep or unsatisfying quality of sleep, is often associated with stress. It impairs function in many areas of life.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument contains 23 items that assess three academic coping strategies: positive reappraisal , understood as a coping strategy aimed at changing the meaning of a problematic situation, highlighting its positive aspects, and activating positive expectations (10 items; e.g., “When I am faced with a problematic situation, I forget the unpleasant aspects and highlight the positive ones”); support‐seeking , which involves both seeking advice and information on how to resolve a problem as well as seeking understanding and support for the emotional state caused by the problem (seven items; e.g., “When I am faced with a problematic situation, I ask for advice from a family member or a close friend”); and planning , which aims at analyzing and designing an action plan intended to solve a problematic situation (six items; e.g., “When I am faced with a difficult situation, I list the tasks that I have to fulfill, I complete them one at a time, and I do not go to the next step until I have completed the previous one”). This three‐component structure has shown good psychometric properties in previous studies of university populations (Freire, Ferradás, Valle, Núñez & Vallejo, ) and exhibited adequate reliability in the present study, with α = 0.87, 0.91, and 0.83 for positive reappraisal, support‐seeking, and planning, respectively. A five‐point Likert scale ranging from 1 ( never ) to 5 ( always ) was used to collect the participants’ responses.…”
Section: Methodsmentioning
confidence: 99%